Mother's opinions concerning the importance of and their satisfaction with support received in the labor and delivery rooms - T Mirmawlai; A Mehran; S Rahimi Gasabeh (Tehran University of Medical Sciences, 2003)
Childbirth is one of the most stressful situations in a woman's life. In order for a woman to adjust to the stress of delivery and to make it a happy experience for her, she should be supported with adequate information as well as emotionally and physically. This research was undertaken to analyze the opinion of mothers concerning the importance of and their satisfaction with information, physical and emotional support received in the labor and delivery rooms. In this descriptive-analytic study 400 post-partum mothers from 10 various training hospitals in city of Tehran in the year 2000 were randomly selected and interviewed by questionnaire in the post-delivery ward. Results showed that most of the mothers placed great importance on physical, informational, and emotional support, respectively. They had received inadequate physical and informational support and relatively adequate emotional support. But most of them were satisfied with the informational, emotional and physical support, respectively. There was no significant association between the level of satisfaction of the mothers with these three types of support and their importance but there was a significant association with the way that support was received. (P<0.05). Complete satisfaction with the support offered, despite their inadequacy or limitations, may be due to the fact that mothers are unaware of their rights and have few expectations or may be due to the time of conducting the interview (just before discharge). The lack of any relation between the demographic variables and the value of importance in the different areas of support shows that these are basic needs and all should be equally provided. In order to increase satisfaction, support and care should be provided to mothers in the best possible fashion. Finally, regarding the presence of midwifery students and their teachers in teaching hospitals, they should be made directly responsible for the reformation of the hospital system, preparation of hospital charts and their organization.